The Nordic Region (Norden) and the Baltic Europe Region in the Begining of 90s of the 20th Century - Kubka, Andrzej (Wydawnictwo Uniwersytetu Gdańskiego, 2014)
According to the following paper, the integration in the Baltic Region seen from the Nordic States perspective was not seen as a goal in itself in the beginning of nineties of the 20th century. It was a part of a broader context of “return to Europe”. One may assume that perception of Baltic cooperation as a first step towards the integration within European Union was typical for nordic perspective. After some time, in the first decade of the 21st century, the context of Baltic integration processes became broadened not only towards European integration, but also globalization. According to the following paper, the integration in the Baltic Region seen from the Nordic States perspective was not seen as a goal in itself in the beginning of nineties of the 20th century. It was a part of a broader context of “return to Europe”. One may assume that perception of Baltic cooperation as a first step towards the integration within European Union was typical for nordic perspective. After some time, in the first decade of the 21st century, the context of Baltic integration processes became broadened not only towards European integration, but also globalization.